The Dharanis of Mahavyutpatti #748: Origin and Formation - Pagel, Ulrich (Buddhist Studies Review, 2007)
This paper aims to identify the sources of a list of twelve dharanis included in Rubric 748 of the Mahavyutpatti. It produces evidence connecting this group with three similar dharani enumerations transmittted in the Ratnamegha, Tathagatagunajñanacintyavisayavataranirdesa and Tathagatamahakarunanirdesa. The exposition of the Tathagatamahakarunanirdesa is particularly valuable since it preserves one of the earliest and most detailed discussions of dharani practice in Mahayana sutras. The Ratnamegha is closest to the Mahavyutpatti and thus the most likely source for its list.